Pengaruh Ketersediaan Fasilitas Belajar terhadap Prestasi Belajar Siswa Kelas V SD - abd kadir; Rahmawati Patta; Evi Muzarrafah (Universtas Negeri Makassar, 2022)
This study aims to determine whether there is an effect of the availability of student learning facilities at home on the learning achievement of fifth graders of SD Gugus II, Tanete Riattang District, Bone Regency. This research is a quantitative research with the type of correlational research with ex post facto model. The population in this study amounted to 136 students with a sample of 68 people, namely 50% of the total population. Data collection using questionnaires and documentation. The results of descriptive statistical analysis describe the availability of student learning facilities at home in the medium category with a frequency value of 45 and a percentage of 66%. While the results of descriptive analysis describe student achievement in the medium category with a frequency value of 51 and a percentage of 75%. statistical results show that rcount is 0.668 while rtable at the 5% significance level is 0.2387 so that rcount is rtable (0.668 0.2387). As for the conclusion, there is a significant effect between the availability of learning facilities at home on the learning achievement of fifth graders of SD Gugus II, Tanete Riattang district, Bone regency.